Brutal International Law: A walk through Marcel Breuer's former American Embassy in The Hague. Issue 1 (March 2020) - Stolk, Sofia; Vos, Renske
In April 2019, an unusual group of artists and international legal academics gathered on an elegant square in The Hague to visit the former American Embassy. This brutalist icon, designed in the 1950s by Marcel Breuer, was recently abandoned by its original inhabitants. The ongoing transition of the building from highly secured embassy to public cultural centre makes for a moment to reflect on the meanings this space inspires. In this special section, we posit the building as a prism through which we probe the connections between art, architecture and international law. In line with the tradition of (re)invention embodied by Breuer's design, the section breathes experimentation. The contributions are eclectic, unconventional and rough round the edges. The section is structured as a route through the building with no particular order or hierarchy. The 'façade' functions as a somewhat natural starting point, thereafter, the reader is invited to choose her own route. All spaces that can be visited are actual spaces in the building and echo the source of inspiration of the contributor. We invite you to join us on our journey and to explore the special issue as you would explore and make sense of an abandoned building where traces of international law abound.